Quantitation of Sitagliptin in Drug Product by Validated Reversed Phase Liquid Chromatographic Technique - Sultana, Sharifa; Hossain, Md Shahadat; Islam, Md Samiul; Rouf, Abu Shara Shamsur (Dhaka University Journal of Pharmaceutical Sciences, 2018)
A novel reversed phase ultra-high performance liquid chromatographic (RP-UHPLC) method was developed for the estimation of sitagliptin in pharmaceutical dosage form. Separation was done by a X-bridge C18 column (4.6 i.d.× 150 mm, 5 μm particle size) with a flow rate of 1 ml/min using phosphate buffer (pH 6) and acetonitrile (70:30, v/v) as mobile phase at 268 nm using photodiode array plus (PDA+) detector. The retention time was found at 4.607 min. The developed method was validated as per the requirements of ICH-Q2B guidelines for specificity, system suitability, linearity, precision, accuracy, sensitivity and robustness. The linear regression analysis data for the linearity plot showed correlation coefficient values of 0.999 with LOD value of 0.06 μg/ml and LOQ of 0.225 μg/ml. The relative standard deviation (%RSD) for inter-day and intra- day precision was not more than 2.0%. The method was found to be accurate with percentages recovery of 98.50±0.03 to 99.70±0.05 and the % RSD was less than 2. The results showed that the proposed method is highly convenient for routine analysis of sitagliptin. Dhaka Univ. J. Pharm. Sci. 17(1): 123-129, 2018 (June)